Health Seeking Behavior of Peri-Urban Community Of Chandkheda - Patel, Prakash; Trivedi, KN; Nayak , SN; Patel , Priyanka (National Journal of Community Medicine, 2010)
The study conducted in peri-urban area, reveals that utilization of government health care facilities was poor in the study area compare to national level surveys. Utilization of public health care facilities was significantly higher in lower socio-economical class. Large number of poor families presently utilizes the services provided by private health providers for a multitude of reasons like long waiting period (53.8%), distance location (50.2%) and inadequate facilities (25.4%) etc, the majority of which can be rectified with minimal resources input.